Banking Internationalisation and the Expansion Strategies of European Banks to Brazil during the 1990s - Luiz Fernando de Paula (SUERF - The European Money and Finance Forum, 2002)
This paper aims at analysing the determinants of the recent wave of European banks to Brazil under the context of the recent phase of banking internationalisation. In its first part, it analyses the process of banking internationalisation from both analytical and historical approach. Focusing on the determinants of the banking internationalisation process, the paper shows that (i) the recent wave of banking internationalisation is characterised not only for financial institutions following their existing relationships, but also and increasingly by a greater integration with the local market; (ii) banks operating in countries where the banking sector is larger and more profitable should be able to export a superior skill and are more likely to expand their activities abroad. The second part of the paper examines the determinants of the expansion of European banks in Brazil, as well as the expansion strategy of the four major European banks in Latin America - BSCH, BBVA, HSBC and ABN-Amro. In this regard, it shows that the recent wave of European banks entering Latin America and Brazil is determined by a set of different factors, that includes the process of restructuring the banking sector under the EMU; the dynamics of the internationalisation of the Spanish banks, since they have been the main players in the recent influx of foreign banks into Latin America; the process of market deregulation in the region since early 1990s, in the broader context of economic and political reforms; the better prospects of the region for increasing returns to financial institution compared to developed countries, as well as the potential gains in efficiency. Besides, it also shows that one of the common features of the four major European banks in Latin America - BSCH, BBVA, HSBC and ABN-Amro - is that all the top 4 are big universal banks that choose to expand abroad as a strategy to expand their activities. More precisely, expanding abroad is not only a source of diversification of earnings, but also a way to strengthen their position in the European banking market under the pressure of economic and monetary union.
Keywords: G15; G21; G34; 330; multinational banks; European banks; banking internationalisation; Brazil; Internationale Bank; Bankgeschäft; Ausländische Tochtergesellschaft; Brasilien; Europa